DAYA TARIK, CITRA DESTINASI, DAN FASILITAS PENGARUHNYA TERHADAP MINAT BERKUNJUNG ULANG PADA OBJEK WISATA WAHANA SURYA BENGKULU TENGAH - Yozi Ardiansyah; Ratnawili Ratnawili (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
This study aims to determine the effect of attraction, destination image, and facilities on interest in revisiting the Wahana Surya Bengkulu Tengah Tourism Object. The number of samples in this study were 70 respondents as samples. Determination of the sample using purposive sampling method with the criteria of the respondents being visitors who have visited at least two times to Wahana Surya Bengkulu Tengah Tourism Object. Data collection by questionnaire method. The data that has been collected is then processed using multiple linear regression, coefficient of determination (R2), t test and f test. Based on the results of multiple linear regression, the regression equation form Y = 4.784 + 0.811 (X_1) + 0.313 (X2) + 0.294 (X3). Which means if the attractiveness variable (X1), destination image (X2), and facilities (X3) on the interest in revisiting (Y) is equal to zero, then the variable interest in revisiting will remain at 4.784. The results of the analysis of the coefficient of determination (R2) obtained a value of 0.671 or 67.1% which means that together the attractiveness variables, destination image, and facilities contribute to influencing the interest in revisiting, while the remaining 0.329 or 32.9% is influenced by other variables that are not enter into research. The results of the t-test for the attractiveness variable (X1) show the value of t_hit>t_(α/2) (4.446 > 1.996) and (sig = 0.000 < 0.050), this shows that there is a positive and significant effect of attractiveness (X1) on interest in revisiting (Y), the destination image variable (X2) shows the value of t_hit>t_(α/2) (2,348 > 1,996) and (sig = 0.022 < 0.050), this shows that there is a positive and significant influence on the interest of the distention image. visit again (Y), and the facility variable (X3) shows the value of t_hit>t_(α/2) (2.256 > 1.996) and (sig = 0.027 < 0.050), this shows that there is a significant effect of facilities on interest in revisiting (Y ). From the results of the f test showing the value of t_hit> t_(α/2) (44.807 > 3.977) and (sig = 0.000 < 0.050), it can be concluded that H_4 is accepted meaning that simultaneously the attractiveness variable (X_1), image distension ( X2) and Facilities (X3) significantly influence the interest in revisiting (Y) at Wahana Surya Bengkulu Tengah Tourism Object. Keywords: Attractiveness, Destination Image, Facilities, Interest of Revisiting.